Anthropometric measurements of term neonates in tertiary care hospital of Wardha district - Amar M. Taksande; Bhavana Lakhkar; Ajit Gadekar (Al Ameen Medical College, 2015)
Objective: The present study was undertaken to find the anthropometric parameter like birth weight (BW), length, occipitofrontal circumference(OFC), midarm circumference(MAC), chest circumference (CC), midthigh circumference(MTC) and maximum calf circumference (MCC) of normal healthy neonates at birth which can be used to draw growth chart. Study design: Hospital based cross-sectional study. This study was done in the pediatric department of AVBRH hospital, Sawangi (Meghe), Wardha from April 2012 to August 2012. Materials and methods: 211 full terms, normal, singleton newborn babies were included BW, length, OFC, MAC, CC, MTC and MCC were taken within 72 hours of birth. Results: Of the 211 neonates 115 (54.5%) were male and 96 (45.5%) female. The mean BW, length, OFC, MAC, CC, MTC and MCC were 2.815(0.28) kg, 51.15(3.31) cm, 33.52(1.92) cm, 10.12(1.30) cm 28.66(2.52) cm, 14.33(1.74) cm and 10.58(1.20) cm respectively. No statistically significant difference was present in the anthropometric parameter of boys and girls. Conclusions: This study establishes local normal values for anthropometric measurements for healthy, full term newborn in wardha district. To develop our population data, community based studies should be conducted regularly.